(untitled) (Medico Legal Update, 2019)
Introduction: Many studies have been conducted on the estimation of stature from different body parts like hands, trunk, vertebrae, extremities and foot. Since, all these parts of the body and also bones are not always available for forensic examination. It becomes now necessary to make use of other parts of the body like head & face region. Determination of stature is considered an important parameter in medico-legal and forensic examinations. Objective: this study was carried out to investigate the possibility of estimating stature from external ear morphometry in a sample of Hyderabad population. Method: This study was carried out on 300 persons (180 males and 120 females). Besides stature, eight measurements were obtained from both ears of each participant using manual vernier caliper. Data were analyzed by SPSS version 16. Results: There was a strong significant positive correlation between all measurements and stature. A linear equation model for prediction of stature from given external ear dimension was generated. By simple linear regression analysis, the most accurate predictable variable of stature from both ears in males was ear length (R² = 0.728 in right ear and R² = 0.815 in left ear). While in females; right ear width (R² = 0.655) and left conchal width (R² = 0.791) are the most accurate variables that can predict stature. Conclusion: it is concluded that external ear morphometry can be used as an additional tool in the estimation of stature in Hyderabad population.